Sustainable Palm Oil Industry: Literature Study with Bibliometric Analysis - Saleh Husin; Hanief Saha Gafur; Mia Siscawati; Yusuf Kristiadi; Auderey G. Tangkudung (Budapest International Research and Critics University, 2021)
This article aims to discuss the latest trends and seek new research on a sustainable palm oil industry. This research is a literature review using Publish or Perish software to search for article data on Google Scholar and using VOSviewer to analyze and visualize the data obtained. The research findings show 3 main group themes of research on the sustainable palm oil industry and based on the research findings, the researcher concludes that the research gap on the sustainable palm oil industry is still very wide open to the themes of institutional industry, producers, and the European Union as well as about the coconut certification system especially in Indonesia.